BMP4 activation and secretion are negatively regulated by an intracellular gremlin-BMP4 interaction. - Sun, J; Zhuang, F; Mullersman, J; Chen, H; Robertson, E; Warburton, D; Liu, Y; Shi, W (2006)
Bone morphogenetic protein 4 (BMP4) is a potent growth factor that is involved in many important biological processes. Regulation of the level of secreted mature BMP4 determines the biological effects of BMP4 on cells in the local microenvironment. Previous studies suggested that Gremlin, a member of DAN family proteins, antagonizes BMP4 activity by sequestering extracellular BMP4. Herein, we report a novel intracellular regulatory mechanism by which Gremlin interacts with BMP4 precursor, prevents secretion of mature BMP4, and therefore inhibits BMP4 activity more efficiently. Furthermore, we also defined a 30-amino acid peptide sequence within the Gremlin DAN domain that is essential for BMP4 interaction. This novel Gremlin-mediated BMP4 posttranslational regulatory mechanism implies that the level of BMP4 mRNA expression does not truly reflect BMP4 activity when Gremlin and BMP4 are coexpressed within the same cell. Similar regulatory mechanisms may be utilized by other DAN family proteins.